Il Il Massiccio Centrale attraverso le sue rappresentazioni letterarie - Marina Marengo (Fabrica Litterarum Polono-Italica)
In this essay we want to investigate the methods as well as the typologies of literary representations relating to the Massif Central, starting from the writers who have chosen this portion of the middle French mountains as the context to set their novels. These are literary works that have the peculiarity of representing the territorialization actions of the inhabitants as well as their ways of life, relationships, and production – of yesteryear or contemporary – of this portion of France starting from the end of the nineteenth century. The enhancement of local literary heritage has contributed to creating new dynamics of local development in the marginal areas of the mountain region in question, such as literary itineraries, literary cafés, writers’ houses, etc.